2020
DOI: 10.1089/jwh.2019.7785
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Volatile Organic Compounds and Use of Feminine Hygiene Products Among Reproductive-Aged Women in the United States

Abstract: Background: Feminine hygiene products (FHPs) are personal care products widely used by women. A few studies have detected some volatile organic compounds (VOCs) in FHPs, but no previous epidemiological studies have linked use of these products to human exposure to VOCs using biomarkers. Therefore, we evaluated whether the use of FHPs was associated with VOC exposures among reproductive-aged women in the United States. Materials and Methods: Data on 2432 women aged 20-49 years from National Health and Nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
0
22
0
2
Order By: Relevance
“…The use of douches, vaginal wipes/towelettes, and vaginal washes/cleaners that was more common among Black women in our study is consistent with previous studies (53,54), demonstrated that greater use of vaginal douches among Black women substantially contributed to racial/ethnic differences in phthalate exposure. Recent testing studies have shown that some menstrual/intimate care products contain EDCs, such as phthalates and parabens, and also VOCs, and that, under certain scenarios, menstrual/intimate care product use may contribute substantially to body burden of phthalates (52,(55)(56)(57). Of even greater potential concern is the use of scented menstrual/intimate care products like scented tampons.…”
Section: Product Use Differences By Race/ethnicitymentioning
confidence: 99%
“…The use of douches, vaginal wipes/towelettes, and vaginal washes/cleaners that was more common among Black women in our study is consistent with previous studies (53,54), demonstrated that greater use of vaginal douches among Black women substantially contributed to racial/ethnic differences in phthalate exposure. Recent testing studies have shown that some menstrual/intimate care products contain EDCs, such as phthalates and parabens, and also VOCs, and that, under certain scenarios, menstrual/intimate care product use may contribute substantially to body burden of phthalates (52,(55)(56)(57). Of even greater potential concern is the use of scented menstrual/intimate care products like scented tampons.…”
Section: Product Use Differences By Race/ethnicitymentioning
confidence: 99%
“…These patterns may reflect differential experiences and thus differential exposures among demographics. Such differential exposures have been previously supported by empirical investigations in women of color (Branch et al 2015;Ding et al 2020;Nguyen et al 2020) and individuals with lower income (van Woerden et al 2019). Further understanding the specific sources of these disparities would be a priority for future research and could include further analyses of the purchasing data to examine both product brand (which in some cases could be a surrogate for store access) and refined product type (which could be used to quantify differences in habits and practices among demographics).…”
Section: Demographic Differencesmentioning
confidence: 80%
“…Humans were at risk of being exposed through environmental, occupational [ 27 , 33 , 57 , 58 ], and other sources, including commercialized consumer products. In the most recent study, Ding et al [ 36 ] conducted a cross-sectional population study to establish an association between exposure to m-xylene and p-xylene, as part of the volatile organic compounds and the application of feminine hygiene products among American women in their reproductive age [ 36 ]. Trace levels of m-xylene and p-xylene were found among women who used vaginal douches for a period of six months.…”
Section: Resultsmentioning
confidence: 99%
“…Trace levels of m-xylene and p-xylene were found among women who used vaginal douches for a period of six months. Ding et al [ 36 ] admitted that the study had several drawbacks in terms of the reliability of the results. The cross-sectional data gathered for their study did not address other possible sources of volatile organic compounds.…”
Section: Resultsmentioning
confidence: 99%